Class II young adult treatment with Twin Force Bite corrector: 10-year follow-up - Ozge Uslu-Akcam; Ayse Tuba Altug; Ufuk Toygar Memikoglu (Wolters Kluwer Medknow Publications, 2017)
One of the most preferred compliance free fixed functional appliances in nongrowing patients is Twin Force Bite corrector (TFBC). The aim of this case report is to evaluate the effectiveness of TFBC in the treatment of an adult Class II case. A 16-year 1-month-old boy having skeletal and dental Class II relationship was selected. Roth 0.018 × 0.025 inch slots brackets were attached; a fixed lingual arch in the mandibular dental arch and a Nance appliance in the maxillary dental arch were used to increase anchorage. The TFBC therapy used for sagittal activation and stimulation of forward mandibular growth lasted for 3 months. The post-TFBC treatment lasted 6 months and the total treatment time was 9 months. Treatment of a young adult Class II malocclusion with TFBC resulted in a Class I molar occlusion, an ideal overjet, overbite, and incisor angulation in a short time and maintained in the 10-year follow-up.